A remarkable new species of spittlebug and a second living New World genus in the Clastopteridae (Hemiptera: Cercopoidea) - Paladini, Andressa; Thompson, Vinton; Bell, Adam J.; Cryan, Jason R. (Zootaxa, 2020)
A new species of Neotropical spittlebug (Hemiptera: Cercopoidea: Clastopteridae), Paraclastoptera erwini sp. n., is described and illustrated from Orellana, Ecuador. This species exhibits unique features differentiating it from all known Clastoptera and serves as the genotype for a new genus Paraclastoptera gen. n. This is the second extant New World genus for the Clastopteridae, hitherto represented solely by the widespread, abundant and speciose genus Clastoptera.